Valoração dos serviços ambientais associada à autodepuração da água do Rio Jaguaribe-CE em um cenário de mudanças climáticas - Studart Filho, Rogério Soliani (2013)
The pollution of water resources, mainly arising from the release of untreated domestic sewage collection system or deficit, raises serious damage to the socioeconomic development, significantly affecting the quality of life. In Brazil, the collection and treatment of sewage are considered precarious. The Management Plan Basin Water Jaguaribe (SRH, 1999) pointed domestic sewage as a major pollution sources in the basin, given that few cities in the basin have public collection system and wastewater treatment. Thus, one can say without a doubt that urban centers in Jaguaribe Basin are potential polluters of their water bodies by domestic sewage, because of lack of adequate system of collection, treatment and final disposal of their effluents in receiving bodies. There are, therefore, the fundamental importance of the environmental service provided by Jaguaribe River and its tributaries dilution and self-purification of organic loads that they are intended. The pricing of this service environment will induce economic agents to calculate the cost-benefit, if they want to use it. In this research, the cost of the environmental service provided by Jaguaribe River was estimated costs for the installation of sewage treatment plants (stabilization ponds), implemented in the State of Ceará, between the years 2008 and 2010. Simulation was performed with the numerical model QUAL2BR. The total estimated remediation costs for the current scenario (2010) was R$ 5.658.365,92. This is the cost that theoretically is provided free of charge by Jaguaribe River the environmental services of selfpurification and dilution of the pollutant effluent. Another analysis that was done, was to analyze the impact of climate change in the self-purification of the water body (in terms of BOD) using two models of climate change: the HadGEM2-AO and CanESM2.